Peran Pemerintah Kotabumi Meningkatkan Perdagangan Internasional Khususnya Ekspor - Rumianti, Susti; Mervita, Eda; Iskandar, Dadang Ishak (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
International trade is the main pillar of the global economy, therefore the government's role is needed to improve the quality and quantity of international trade, especially exports, by implementing import duty exemption policies and providing incentives for MSMEs. The government must also be able to take advantage of the potential for market expansion and improve people's welfare. However, strict supervision of imports is also needed to protect domestic industry from the negative impacts of international trade. The government needs to use various instruments, such as tariffs and import quotas, to strike a balance between protecting local industry and meeting domestic needs. Free trade agreements are also an important instrument for opening wider market access. This research highlights the key role of government in managing the dynamics of international trade for sustainable economic growth and societal welfare. Keywords : International Trade, Government, Export